Regularization of peat humic acids functional composition; E3S Web of Conferences; Vol. 98 : 16th International Symposium on Water-Rock Interaction (WRI-16) and 13th International Symposium on Applied Isotope Geochemistry (1st IAGC International Conference) - Chukhareva N. V. Natalia Vyacheslavovna (2019, 2019)
Title screen